Differential expression of HAVCR2 gene in pan-cancer: A potential biomarker for survival and immunotherapy - Li, Hetong; Yang, Dinglong; Hao, Min; Liu, Hongqi (Frontiers in Genetics, 2022)
T-cell immunoglobulin mucin 3 (TIM-3) has emerged as a promising immune checkpoint target in cancer therapy. However, the profile of the hepatitis A virus cellular receptor 2 (HAVCR2) gene, encoding TIM-3 expression, is still obscure, along with its role in cancer immunity and prognosis. This study comprehensively analyzed HAVCR2 expression patterns in pan-cancer and underlined its potential value for immune checkpoint inhibitor-based immunotherapy. Our results displayed that HAVCR2 was differentially expressed and closely corresponded to survival status in pan-cancer. More importantly, the HAVCR2 expression level was also significantly related to cancer immune infiltration, immune checkpoint genes, and immune marker genes. Enrichment analyses implicated HAVCR2-associated terms in cancer, including immunity, metabolism, and inflammation. Our study demonstrated that HAVCR2 could participate in differing degrees of immune infiltration in tumorigenesis. The highlights of the HAVCR2 pathway revealed that TIM-3 could function as both a biomarker and clinical target to improve the therapeutic efficacy of immunotherapy.